The participatory selection of priority climate-resilient value chains for dryland mixed farming systems in Senegal - Dizyee, Kanar; Houessionon, Prosper; Ouédraogo, Issa; Jaquet, Stéphanie; Kumar, Shalander; Chan, Derek; Faye, Aliou; Diouf, Binta; Ndjido, Kane; Zougmoré, Robert B.; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
In support of the implementation of the AICCRA project in Senegal, an analysis of dryland cereal and livestock value chains was conducted. The AICCRA project envisions to increase access among agriculture research and extension providers in Africa to knowledge, technologies, and decision making tools for climate resilience. The analysis resulted in the identification of two priority value chains for cereal and livestock, namely: millet, peanut, cattle, and dairy. This report presents the results of a three-step process was followed for this analysis: (1) holding a participatory workshop with stakeholders ranking priorities, value chains, and to build a quantifiable ranking system to compare the value chains, (2) process and analyze workshop information, and (3) identify the value chains for further work and reporting. Within the two-day participatory workshop that was conducted from 15th-16th June 2021 in Thiès, Senegal with representatives from diverse crop and livestock value chains, government, and non-governmental organization partners, (i) criteria for ranking were listed and weighted, (ii) value chains were identified, and (iii) value chains were prioritized based on the criteria. Moving forward, the AICCRA Senegal cluster will collect further data on the value chains of identified for quantitative assessments to enable the implementation of climate resilient solutions.